Interactive Digital Maps for Early Childhood Islamic Learning - Abdul Malek, Aida Shahira; Ahmad, Mazida; Katuk, Norliza (Multidisciplinary Applied Research and Innovation, 2021)
The capability of displaying the infographics and visualizations methods represent the significance of this system in illustrating a story using pictures, text, or voice in a manner that kids can understand and be attentive. The infographics can help the kids to understand the information more easily. The web-based system provides a new way of learning Islamic education by providing relevant age-appropriate knowledge for kids or lower primary school children. The content portrays the journey of Prophet Muhammad in an interesting and attractive manner supported by the geographic infographics design. Digital maps were chosen to construct the infographics knowledge. The purpose of this study is to develop an interactive digital map web-based system for young kids. The system can be a support tool for kids, particularly in addressing problems related to learning boredom. The children learning progress will be affected if they cannot comprehend complicated material. The system was developed using the Prototyping methodology. The system requirements were evaluated by primary kids, teachers, and parents using a questionnaire. The results indicate positive feedback and signify that the Salam Muhammad website is user-friendly and beneficial. The system offers an interactive platform that can improve children's thinking and learning skills.